Nutrient Content of Pleurotus pulmonarius (Fr.) Quel. Grown on Some Local Lignocellulosic Wastes - Akyuz, Mehmet; Inci, Sule; Kirbag, Sevd (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2022)
The aim of study as to determine the effects of some composts on the nut ritional value of Pkurotus pulmonarius (Fr.) Quel. The energy, dry mat ter. moisture. crude protein, fat, ash, organic matter, and nitrogen free extract were 311.3-313.9 (kcal 100 g(-1)), 91.8-92.5, 7.5-8.2, 27.3-1-38.6, 1.5-1.9, 5.3-6.4, 35.9-46.8 and 86.0-87.1 (g 100 g(-l)) of dry weight. respectively. The contents of polymeric substance were determined 13.6-16.2% of cellulose, 20.4-21.8% of hemicellulose and 0.1-0.3% of lignin. It was observed that the crude fat, energy, lignin and hemicellulose contents Of P pulmonarius were not statistically significant depending on the substrates used in the culture (p>0.05), but there were variations in other nutrients (p<0.05). It is highly valued as a good source of proteins. energy and carbohydrates. but rather low in their fat., lignin and hemicellulose contents. It supports that the substrate products used in t he culture of P. pulmonarius can affect the nutrient composition of the mushroom such as energy, crude protein and carbohydrate.
Keywords: Nutritive value; Pleurotus pulmonarius; Lignocellulosic wastes; Cultivation; Edible mushrooms